Endocrinopathies and cancer cachexia. Issue 4 (December 2019) - Dev, Rony; Del Fabbro, Egidio; Dalal, Shalini
Abstract : Purpose of review: Cancer cachexia cannot be easily reversed by standard nutritional support and interventions directed at underlying metabolic derangements may be needed to prevent or reverse cachexia and maintain healthy body composition. The following review will highlight the contribution and potential therapeutic interventions for insulin resistance, alterations in ghrelin signaling, and hypogonadism in cancer patients. Recent findings: In addition to decreased caloric intake, chronic inflammation, and altered metabolism of glucose, proteins and lipids, endocrine abnormalities can propagate weight loss or changes in body composition in cancer patients. Summary: Cancer cachexia, loss of muscle mass with or without the loss of fat mass, is a multifactorial syndrome, which is associated with increased morbidity and mortality. Currently, limited therapeutic options for the treatment of weight loss in cancer patients exist, which lead to clinically meaningful improvements in weight gain and performance status. Treatment directed at underlying insulin resistance, low testosterone, and altered ghrelin sensitivity, in the future, may lead to potential therapeutic options for loss of lean body mass and cancer cachexia.